THE IMPLEMENTATION OF TEACHING SPEAKING BY USING VERBAL MOTIVATION â€œYES, I CANâ€ STRATEGY FOR THE ENGLISH BEGINNERS IN THE FOUNDATION SPEAKING CLASS AT PEACE ENGLISH ACADEMY - Shobaha, Shohiyah (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research is to describe the implementation of teaching speaking by using verbal motivation â€œYES, I CANâ€ strategy for the English beginners in the foundation speaking class at PEACE English Academy. The research focuses on the background of using verbal motivation â€œYES I CANâ€ strategy, the implementation of verbal motivation â€œYES I CANâ€ strategy in the terms of; lesson plan, technique, intensity,problem â€“ solving, studentsâ€™ respond, and the speaking achievement of the students. This research was conducted at PEACE Pare Kediri. The methodology used in this case was qualitative research. It means the data gotten were described qualitatively. The subjects of this research were the director, the teacher and students of foundation speaking class at PEACE. Data collection methods were observation, interview, questionnaire, and documentation. To analyze the data, the researcher used data display, data reduction, verification and triangulation. This research resulted that this implementation was to build studentsâ€™ self-confidence to speak, the teacher uses lesson plan in form of simple list materials, the technique used by using the key word â€œPEACE STUDENTâ€ and all students answer â€œYES, I CANâ€ while rising their hands up, the intensity in implementing is three times per meeting: in opening, before practice and before closing, the problem rises form internal factor when the students are of lack of energy, the solution is by giving verbal motivation â€œYES, I CANâ€ more or giving moving brainstorming and game. Students got what they need in learning process through this strategy, andthe students get predicate A (very good) in fluency is 56 %, in understanding is 52%, in accent is 4 %, and in vocabulary is 64%.   The students who got predicate B (good) in fluency is 44 %, in understanding is 48%, in accent is  96%, and in vocabulary is 36%, C and D are 0 %. So, all of the students were successful because their score were above the standard minimum acquisition value from the teacherâ€™s determination.